A Bi-level Framework for Understanding Prisoner Victimization - Wooldredge, John (Journal of quantitative criminology, 2014)
Objectives To present and test an opportunity perspective on prison inmate victimization. Methods Stratified random samples of inmates ( n _1 = 5,640) were selected from Ohio and Kentucky prisons ( n _2 = 46). Bi-level models of the prevalence of assaults and thefts were estimated. Predictors included indicators of inmate routines/guardianship, target antagonism, and target vulnerability at the individual level, and several indicators of guardianship at the facility level. Results Assaults were more common among inmates with certain routines and characteristics that might have increased their odds of being victimized (e.g., less time spent in recreation; committed violence themselves during incarceration), and higher levels of assaults characterized environments with lower levels of guardianship (e.g., architectural designs with more “blind spots”, larger populations, and less rigorous rule enforcement as perceived by correctional officers). Similar findings emerged for thefts in addition to stronger individual level effects in prisons with weaker guardianship (e.g., ethnic group differences in the risk of theft were greater in facilities with larger populations and less rigorous rule enforcement). Conclusions The study produced evidence favoring a bi-level opportunity perspective of inmate victimization, with some unique differences in the relevance of particular concepts between prison and non-prison contexts.